2015
DOI: 10.1177/0269881114565937
|View full text |Cite
|
Sign up to set email alerts
|

Repeated administration of aripiprazole produces a sensitization effect in the suppression of avoidance responding and phencyclidine-induced hyperlocomotion and increases D2 receptor-mediated behavioral function

Abstract: The present study investigated how repeated administration of aripiprazole (a novel antipsychotic drug) alters its behavioral effects in two behavioral tests of antipsychotic activity and whether this alteration is correlated with an increase in dopamine D2 receptor function. Male adult Sprague-Dawley rats were first repeatedly tested with aripiprazole (3, 10 and 30 mg/kg, subcutaneously (sc)) or vehicle in a conditioned avoidance response (CAR) test or a phencyclidine (PCP) (3.20 mg/kg, sc)-induced hyperlocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…The dose of aripiprazole (10 mg/kg) was determined based on previous studies in our lab (Gao et al, 2015; Li et al, 2005) and reports in the literature (Carli et al, 2011; Cosi et al, 2006; Li et al, 2004). This dose of aripiprazole was chosen because it results in 85% occupancy, respectively, at one hour post-injection (Natesan et al, 2006), but does not cause catalepsy (Hirose et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The dose of aripiprazole (10 mg/kg) was determined based on previous studies in our lab (Gao et al, 2015; Li et al, 2005) and reports in the literature (Carli et al, 2011; Cosi et al, 2006; Li et al, 2004). This dose of aripiprazole was chosen because it results in 85% occupancy, respectively, at one hour post-injection (Natesan et al, 2006), but does not cause catalepsy (Hirose et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…One dose of OLZ (.5 mg.kg) and one dose of CLZ (5 mg/kg) were tested. It has been demonstrated that repeated OLZ treatment causes sensitization, whereas repeated CLZ causes tolerance in both adolescent and adult rats (Gao, Qin & Li, 2015). These doses were tested to determine how ARI sensitization would affect OLZ and CLZ exposure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations